Coexistence of acute poststreptococcal glomerulonephritis and acute rheumatic fever in a Japanese girl with primary Sjögren's syndrome. (2nd July 2020) - Kobayashi, Ichiro; Takezaki, Shunichiro; Tozawa, Yusuke; Ueki, Masahiro; Hayashi, Asako; Yamazaki, Takeshi; Sato, Yasuyuki; Okamoto, Takayuki; Yamada, Masafumi; Ariga, Tadashi
Abstract: Although acute poststreptococcal glomerulonephritis (APSGN) and acute rheumatic fever (ARF) are well-known complications of group A streptococcus infection, concomitant occurrence of both diseases is rare. We report an 11-year-old Japanese girl with primary Sjögren's syndrome complicated by acute renal failure about 2 weeks after the onset of pharyngitis. Although histopathological findings of the kidney were not confirmative, APSGN was suggested by the spontaneous recovery of her renal function, typical latent period with high levels of antistreptolysin O and low serum levels of C3 but not of C4. In addition, cardiac hypomotility and regurgitation of the 4 valves progressed in the convalescent phase of APSGN, which was accompanied by elevation of serum C-reactive protein and plasma brain natriuretic peptide (BNP) levels. Myocarditis was suggested by delayed gadolinium-enhancement of cardiac walls on cardiac magnetic resonance imaging. She was diagnosed with APSGN and ARF and was treated with a combination of short course prednisolone and prophylactic penicillin G. There is no relapse of renal or cardiac symptoms during 6 years follow-up. Unexpected elevation of plasma BNP in a convalescent stage of APSGN suggests the development of ARF. Underlying Sjögren's syndrome (SS) may modify the histopathological findings and make it difficult to differentiate APSGN from CTD-associated nephritis such as lupus nephritis (LN) even by renal biopsy.